Imaging of Pelvic Floor Dysfunction - Eapen, Anu; Lakhani, Aisha; Hiriyanna, Sneha; Natarajan, Shobiga; Cecil, Goldwin H.; Eapen, Kurian; Pravin, Nithish; Yadav, Saloni; Simon, Betty; Chandramohan, Anuradha (Journal of Gastrointestinal and Abdominal Radiology, 2025)
The pelvic floor, which is divided into anterior, middle, and posterior compartments, receives support from muscles, endopelvic fascia, and ligaments that support the pelvic organs and prevent organ prolapse. Deficiency in the musculofascial support system leads to pelvic floor dysfunction with a wide range of symptoms such as urinary incontinence, fecal incontinence, organ prolapse, and dyspareunia. Imaging has an established role in evaluating pelvic floor dysfunction. Imaging modalities range from conventional imaging, such as fluoroscopic defecography and dynamic colpocystography, to ultrasound and magnetic resonance imaging. Magnetic resonance defecography is particularly useful as it helps to detect multicompartmental involvement, which helps in meticulous surgical planning. This article provides an initial review of pelvic floor anatomy, followed by the role of imaging to assess disorders in each pelvic compartment.
Keywords: pelvic floor; compartment; prolapse; defecography